Accidentally dead, again eaudiobook - Cassidy, Dakota (Accidentally Paranormal, 2014)
After a wild work-sponsored Halloween party, entomologist Sam McLean wakes up with a spotty memory—and a pointy set of fangs. Sam's one-night stand wasn't just dressed as a vampire; she had the bite to match. Somehow, Sam's unconscious body ends up at the OOPS office, where paranormal crisis counselors Nina, Marty, and Wanda give him the down-low on accidentally becoming a creature of the night. Dealing with a newbie like Sam is no easy task, but things get even more crazy when Phoebe Reynolds—a woman who claims to be Nina's sister—storms into the office and causes a catfight that ends when Phoebe is accidentally bitten by Sam's recently formed fangs. Now the OOPS girls have two fledgling vamps on their hands, and their powers—and the attraction building between them—are unlike anything they've seen before.